Associative property of multiplication means that it doesn't matter where the parentheses are placed because it will still be the same answer.
So your answer would be 1, 4 x (3 x 6) = (4 x 3) x 6
I hope this helps!
Answer:
- 0.8
Step-by-step explanation:
The first thing we want to do here is simplify the expression -
( 2x + 5 ) - 2x, Distribute the "
" to elements within the parenthesis
=
2x +
5 - 2x, Focus on simplifying the expression "
2x +
5 "
=
- 2x
=
- 2x, Combine fractions
=
+ 3
=
x + 3
So we have our simplified expression "
x + 3, " with
being the coefficient of x. Our requirements are that this fraction should be expressed as a decimal, so we can simply divide the numerator by the denominator to figure that out,
- 4 / 5 = - 0.8,
Solution = - 0.8
Answer:
x = 5/2 , y = -7/2
Step-by-step explanation:
<em>r's</em><em> your</em><em> solution</em>
<em> </em><em> </em><em>=</em><em>></em><em> </em><em>formula</em><em> </em><em>for</em><em> </em><em>finding</em><em> </em><em>midpoint</em><em> </em><em>=</em><em>.</em><em>(</em><em> </em><em>X1</em><em> </em><em>+</em><em> </em><em>X</em><em>2/</em><em>)</em><em>/</em><em>2</em><em> </em><em>,</em><em> </em><em>(</em><em>Y1+</em><em>Y2)</em><em>/</em><em>2</em>
<em>=</em><em>></em><em> </em><em>putting</em><em> </em><em>the </em><em>value</em><em> </em><em>of </em><em>in </em><em>formula</em>
<em> </em><em> </em><em>=</em><em>></em><em> </em><em>x=</em><em> </em><em> </em><em>4</em><em>+</em><em>1</em><em>/</em><em>2</em><em> </em><em>,</em><em> </em><em>y </em><em>=</em><em> </em><em>-</em><em>1</em><em>-</em><em>6</em><em>/</em><em>2</em>
<em>=</em><em>></em><em> </em><em>x </em><em>=</em><em> </em><em>5</em><em>/</em><em>2</em><em> </em><em>,</em><em> </em><em>y </em><em>=</em><em> </em><em>-</em><em>7</em><em>/</em><em>2</em>
<em>hope</em><em> it</em><em> helps</em>
Answer:
-127
Step-by-step explanation:
first multiplied the ones in parentheses
12+5-144
then you add
12+5=17
17-144=-127